Analysis of the rotation angle of a coupler used on heavy haul locomotives. (November 2014) - Xu, Ziqiang; Ma, Weihua; Wu, Qing; Luo, Shihui
Increases in train length and axle loads have significantly increased in-train forces for heavy haul trains. These forces when combined with the rotation behavior of the coupler can exert an adverse effect on the operational safety of trains. This paper analyzes the rotation behavior of a coupler resulting from the application of a compressive force. A suitable free-rotation angle for the coupler and a stabilization mechanism are also presented. Simulations were performed using a dynamic model of a train consisting of three heavy haul locomotives and two couplers. The obtained results indicate that trains with free-rotation angles of the coupler of 6°have a better dynamic safety and lower levels of wheel tread wear than trains with an initial free-rotation angle of 8°. Variation of the locomotive's structural parameters, including the secondary stop free clearance, the distance between front and rear stops and the distance between secondary stop and coupler pin, affects the maximum rotation angle of the coupler and, in turn, the operational safety of the train. The matching of the locomotive's structural parameters and the free-rotation angle of the coupler should be considered when selecting a heavy haul coupler and buffer system so as to avoid safety problems caused by excessive rotation behavior of the coupler.